Agricultural Innovation Data Hub (AIDH): Empowering Farmers, Strengthening Extension, Building Climate Resilience - Wilson, Michael; Tepa Yotto, Ghislain; Dalaa, Mustapha Alasan; Martey, Francisca; Awotwi, John; Yeboah, Stephen (2025)
This report presents a summary of enhancements for the Agricultural Innovation Data Hub (AIDH), previously known as the Ag-Data Hub. The AIDH has evolved from a data exchange platform to a comprehensive digital ecosystem delivering climate-smart agricultural advisories, decision support tools, and extension services directly to farmers across Ghana's agricultural landscapes. In 2025, implementation has focused on three strategic pillars: enhancing platform interoperability through API development, strengthening accessibility through multimedia content integration, and scaling impact through capacity building and stakeholder engagement. The AIDH now serves as the backbone for digital extension delivery, reaching thousands of farmers daily with timely, localised, and scientifically validated agricultural advisories.